2005
DOI: 10.1152/ajpendo.00196.2004
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effect of the ghrelin agonist growth hormone-releasing peptide-2 (GHRP-2) in arthritic rats

Abstract: Chronic arthritis induces hypermetabolism and cachexia. Ghrelin is a gastrointestinal hormone that has been proposed as a treatment to prevent cachexia. The aim of this work was to examine the effect of administration of the ghrelin agonist growth hormone-releasing peptide-2 (GHRP-2) to arthritic rats. Male Wistar rats were injected with Freund's adjuvant, and 15 days later arthritic and control rats were daily injected with GHRP-2 (100 microg/kg) or with saline for 8 days. Arthritis induced an increase in ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
122
1
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(135 citation statements)
references
References 46 publications
8
122
1
4
Order By: Relevance
“…The decrease in serum leptin and its gene expression in arthritic rats has previously been described in different models of experimental arthritis (Hultgren & Tarkowski 2001, Granado et al 2005a, Stofkova et al 2006. A decrease in leptin secretion has also been reported in humans with other chronic inflammatory illnesses, such as tuberculosis or inflammatory bowel disease (van Crevel et al 2002, Karmiris et al 2006.…”
Section: Discussionmentioning
confidence: 69%
“…The decrease in serum leptin and its gene expression in arthritic rats has previously been described in different models of experimental arthritis (Hultgren & Tarkowski 2001, Granado et al 2005a, Stofkova et al 2006. A decrease in leptin secretion has also been reported in humans with other chronic inflammatory illnesses, such as tuberculosis or inflammatory bowel disease (van Crevel et al 2002, Karmiris et al 2006.…”
Section: Discussionmentioning
confidence: 69%
“…18 In addition, ghrelin has several antiinflammatory properties and decreases neuronal apoptosis. [19][20][21][22] Antioxidant properties of ghrelin have also been demonstrated in recent studies. [23][24][25] Therefore, the aim of this study was to evaluate the effects of ghrelin on the blood levels of MDA and TAC and brain levels of MDA, SOD, GPx and CAT in the normobaric systemic hypoxia situation in rats.…”
Section: Introductionmentioning
confidence: 79%
“…Similarly, ghrelin has been reported to decrease nitric oxide production by peritoneal macrophages (Granado et al, 2005) and to decrease high glucose-induced apoptosis of endothelial cells and apoptosis induced by oxygen-glucose deprivation in hypothalamic neuronal cells through reactive oxygen species inhibition (Chung et al, 2007;Zhao et al, 2007). Moreover, it has recently been reported that UCP2 mediates ghrelin's orexigenic effect on NPY/AgRP neurons by lowering free radicals (Andrews et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, anti-inflammatory and anti-apoptotic actions of ghrelin have been reported in different organs and tissues Dixit et al, 2004;Granado et al, 2005;Granata et al, 2006).…”
Section: Introductionmentioning
confidence: 99%